Supply restrictions, subprime lending and regional US housing prices - André Kallåk Anundsen; Christian Heebøll (University of Oslo, Department of Economics, 2013)
This paper analyzes the recent boom-bust cycle in the US housing market from a regional perspective. Particular attention is paid to supply side restrictions and financial accelerator effects related to subprime lending. Considering 248 Metropolitan Statistical Areas across the entire US, we estimate a simultaneous boom-bust system for housing prices and supply. The model includes non-linear regional specific supply elasticities, determined by geographical and regulatory supply restrictions. In contrast to the predictions of a supply-demand framework, our results suggest that tighter supply restrictions lead to both a larger housing price boom and bust following a temporary increase in subprime lending. Extending the model to include a financial accelerator, our results indicate that supply restricted areas are significantly more exposed to this mechanism, which explains the greater housing price volatility in these areas over the course of a boom-bust cycle.
Keywords: E44; E32; G21; 330; regional boom-bust cycles; housing supply restrictions; subprime lending; financial accelerator